Education System in Egypt - Dinelti Fitria; Berry Devanda; Wienda Gusta; Nurhizrah Gistituati; Rusdinal; Azwar Ananda (CV. AFDIFAL MAJU BERKAH, 2022)
This research aims to know the educational system of the Arab Republic of Egypt. The research method is literature review or literature study, which contains theories relevant to research problems. The result of the educational system of Egypt that the educational objectives are uphold democracy and the formation of democratic individuals. The authority is centralized, under the ministry of education and ministry of Al-Azhar. Curriculum preparation is carried out with teamwork consisting of experts, professors, consultants, and educational supervisors as well as experienced teachers. The government budgets 17% of the national budget. The educational structures are 1) basic education (ibtida'i), 2) secondary education/preparation (I'dadi), 3) upper secondary education (tsanawi), 4) higher education or university, and 5) elementary school level 6-11 years. The academic year start from June to August.